Cytotoxic compounds from Dysoxylum gaudichaudianum (A. Juss.) Miq. - De Los Reyes, Mariquit M. (Animo Repository, 2016)
© 2016, International Journal of Pharmacognosy and Phytochemical Research. All rights reserved. Squalene (1), polyprenol (2), triglycerides (3), and β-sitosterol (4), isolated from the dichloromethane extract of the leaves of Dysoxylum gaudichaudianum, were evaluated for their anti-proliferative activities against three human cancer cell lines, breast (MCF-7) and colon (HT-29 and HCT-116), and a normal cell line, human dermal fibroblast neonatal (HDFn) using the in vitro PrestoBlue® cell viability assay. The HT-29 cell line was most susceptible to the compounds tested. Squalene (1) and polyprenol (2) were most cytotoxic against HT-29 (IC50 of 0.84 and 1.059 μg/mL, respectively), followed by MCF-7 (IC50 of 4.404 and 3.786 μg/mL, respectively), and HCT-116 (IC50 of 7.859 and 9.258 μg/mL, respectively). Triglycerides (3) was highly anti-proliferative against HT-29 cells (IC50 of 2.738 μg/mL) and moderately inhibitory against HCT-116 and MCF-7 cells (IC50 of 13.05 and 16.12 μg/mL, respectively). β-Sitosterol (4) was most cytotoxic against HT-29 and MCF-7 (IC50 of 1.41 and 2.277 μg/mL, respectively) and moderately cytotoxic against HCT-116 (IC50 of 11.63 μg/mL). Comparing the cytotoxic effects of these compounds against the three cancer cell lines, 1-4 were most cytotoxic against HT-29. Compounds 1, 2 and 4 were less inhibitory to MCF-7 and least inhibitory to HCT-116. Comparing the effects of 1-4 on the two colon cancer cell lines, their IC50 values against HT-29 were lower than those of HCT-116. Compounds 1-4 showed moderate cytotoxicity against HDFn cells (11.18 to 17.72 μg/mL) and were less cytotoxic to the normal cells than the cancer cells.